KUALITAS PELAYANAN PUBLIK PADA KANTOR LURAH DI KECAMATAN SELUMA KABUPATEN SELUMA - Dani, Rahiman; K, Pindi; Alexsander, Alexsander; Noviyanto, Hernowo (SENGKUNI Journal (Social Science and Humanities Studies), 2023)
This study aims to identify the quality of community services at the Lurah Office in Seluma District, Seluma Regency, Bengkulu Province, and explain the factors that influence the quality of community services at the Lurah Office in Seluma District, Seluma Regency, Bengkulu Province. This research is descriptive research with a qualitative approach. The determination of subjects in the study was carried out by purposive sampling and snowball sampling methods. There were 12 (twelve) research subjects, namely Talang Saling Village Head, Dusun Baru Village Head, Pasar Tais Village Head, and 3 (three) people who use public services from each Lurah Office. From the analysis using the tangible dimension, the reliability dimension, the responsiveness dimension, the assurance dimension, the empathy dimension, and the factors that influence the quality of public services, it can be explained that the tangible dimension ( tangible) At the Lurah Office in Seluma District it has not implemented well regarding the comfort of the place, ease of service, discipline of officers, ease of access and use of assistive devices. Dimensions of Reliability (reliability), the Lurah Office in Seluma District is still lacking regarding unclear service standards, the ability of officers is still lacking, and there is no expertise possessed by service officers. Responsiveness dimension (response/response), At the Lurah Office in Seluma District, the service process is not smooth and timely, so service users do not feel comfortable. Assurance dimension (guarantee), the Lurah Office in Seluma District does not have timely guarantees for service users but there is no cost for bureaucracy in services. The Empathy Dimension, Officers at the Lurah Office in Seluma District serve the community in a friendly and polite manner, but officers still prioritize their interests over the interests of service users. Two factors influence the quality of public services, namely internal factors and external factors. The internal factors are inadequate infrastructure, lack of service personnel, and lack of tools. While external factors, namely service patterns and procedures for providing services that have not been maximized.